Carbon dioxide enrichment: a technique to mitigate the negative effects of salinity on the productivity of high value tomatoes - Maria J. Sánchez-González; Maria C. Sánchez-Guerrero; Evangelina Medrano; Manuel E. Porras; Esteban J. Baeza; Pilar Lorenzo (Spanish Journal of Agricultural Research, 2016)
The present study was conducted to determine the mitigating influence of greenhouse CO2 enrichment on the negative effects of salinity in Mediterranean conditions. Hybrid Raf (cv. Delizia) tomato plants were exposed to two salinity levels of the nutrient solution (5 and 7 dS/m) obtained by adding NaCl, and two CO2 concentrations (350 and 800 μmol/mol) in which CO2 enrichment was applied during the daytime according to a strategy linked to ventilation. Increasing water salinity negatively affected the leaf area index (LAI), the specific leaf area (SLA), the water use efficiency (WUE), the radiation use efficiency (RUE) and dry weight (DW) accumulation resulting in lower marketable yield. The high salinity treatment (7 dS/m) increased fruit firmness (N), total soluble solids content (SSC) and titratable acidity (TA), whereas pH was reduced in the three ripening stages: mature green/breaker (G), turning (T), and pink/light red (P). Also, the increase in electrical conductivity of the nutrient solution led to a general change in intensity of the sensory characteristics of tomato fruits. On the other hand, CO2 enrichment did not affect LAI although SLA was reduced. RUE and DW accumulation were increased resulting in higher marketable yield, through positive effects on fruit number and their average weight. WUE was enhanced by CO2 supply mainly through increased growth and yield. Physical-chemical quality parameters such as fruit firmness, TA and pH were not affected by CO2 enrichment whereas SSC was enhanced. Greenhouse CO2 enrichment did mitigate the negative effect of saline conditions on productivity without compromising organoleptic and sensory fruit quality.